Diagnostic Accuracy of GeneXpert in Comparison with Histopathological and Microbiological findings in Children with Suspected Tuberculous Lymphadenitis - Bintul Huda, Sonia Saleem, Muhammad Naeem, Ijaz Mohammad, Maira Nazar, Najam Ul Huda, (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To determine the diagnostic accuracy and relationship between GeneXpert MTB/RIF assay, histopathological findings, and microbiological results in children with suspected tuberculous lymphadenitis. Study Design: Cross-sectional study. Place and Duration of Study: Pediatric Department, Gulab Devi Hospital, Lahore, Pakistan, from April 2023 to September 2023. Material and Methods: A total of 50 children aged 2–14 years with suspected tuberculous lymphadenitis were enrolled using non-probability consecutive sampling. Clinical data were recorded using a structured questionnaire. Lymph node samples were obtained through fine needle aspiration cytology or biopsy and subjected to histopathological examination. Microbiological evaluation included acid-fast bacilli smear microscopy, and molecular testing was performed using GeneXpert MTB/RIF assay. Chest X-ray was carried out in all patients. Data were analyzed using SPSS version 25. Chi-square and Fisher’s exact tests were applied to assess associations between variables, and independent sample t-tests were used to compare diagnostic modalities. A p-value of <0.05 was considered statistically significant. Results: The majority of patients were aged 10–13 years (76%). Fever was present in 76% and lymph node enlargement in 88% of cases. AFB smear was positive in 6% of patients, while GeneXpert detected Mycobacterium tuberculosis in 58% of cases. Histopathological examination revealed granulomatous inflammation with caseous necrosis in 26% and without necrosis in 24% of cases, while 12% showed features suggestive of malignancy. Chest X-ray findings were suggestive of tuberculosis in 48% of patients. Statistically significant associations were observed between GeneXpert, microbiological findings, and histopathological outcomes (p<0.05). Conclusion: GeneXpert MTB/RIF assay demonstrates higher diagnostic yield compared to smear microscopy and shows significant correlation with histopathological findings in pediatric tuberculous lymphadenitis. A combined diagnostic approach using molecular, histopathological, and microbiological methods improves diagnostic accuracy and helps avoid unnecessary empirical treatment. Keywords: Tuberculous lymphadenitis, GeneXpert MTB/RIF, Fine needle aspiration cytology, Extrapulmonary tuberculosis, Pediatric tuberculosis.